Pediatric Anterior Cruciate Ligament Reconstruction: A Systematic Review of Transphyseal Versus Physeal-Sparing Techniques. (February 2017) - Pierce, Todd P.; Issa, Kimona; Festa, Anthony; Scillia, Anthony J.; McInerney, Vincent K.
Background: Anterior cruciate ligament reconstruction is becoming more common in skeletally immature individuals, and it may be performed with transphyseal or physeal-sparing techniques. A number of studies have assessed the outcomes of these techniques, but there is a need to systematically evaluate the pooled data from these studies. Purpose: To compare the differences in demographics and outcomes of transphyseal and physeal-sparing techniques by assessing (1) demographics, (2) incidence of growth disturbances, and (3) graft survivorship in the pediatric population. Study Design: Systematic review. Methods: A thorough review of 3 databases was performed to identify all studies that evaluated outcomes after pediatric reconstruction based on transphyseal or physeal-sparing techniques. After completing our search and cross-referencing for additional sources, 43 reports were identified for this review. Reports were analyzed for differences in demographics as well as incidence of leg-length discrepancies, angular deformities, and graft survivorship. After review of manuscripts, 27 studies were included for review (21 transphyseal and 6 physeal-sparing studies). Results: Those who had transphyseal reconstruction were more likely to be female (39% vs 20%; P = .0001), while those with the physeal-sparing surgery were younger (12 vs 13.5 years of age; P = .0001). The transphyseal and physeal-sparing cohorts demonstrated similar incidence rates of leg-length discrepancies (0.81% vs 1.2%, respectively; P = .64) and angular deformities (0.61% vs 0%, respectively; P = .36). The transphyseal and physeal-sparing cohorts also showed similar rates of rerupture (6.2% vs 3.1%, respectively; P = .11). Conclusion: Although the study groups were not well matched with regard to age and sex, our results show that these surgical techniques have no differences in incidence of growth disturbances or graft survivorship. Younger males tend to undergo physeal-sparing reconstruction. Future research should focus on long-term outcome metrics with the physeal-sparing techniques, as there remains a paucity of studies regarding them.